2019
DOI: 10.1002/cbdv.201900400
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances of Natural Polyphenols Activators for Keap1‐Nrf2 Signaling Pathway

Abstract: The Keap1‐Nrf2/ARE signaling pathway is an important defense system against exogenous and endogenous oxidative stress injury. The dysregulation of the signaling pathway is associated with many diseases, such as cancer, diabetes, and respiratory diseases. Over the years, a wide range of natural products has provided sufficient resources for the discovery of potential therapeutic drugs. Among them, polyphenols possess Nrf2 activation, not only inhibit the production of ROS, inhibit Keap1‐Nrf2 protein–protein int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
107
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(111 citation statements)
references
References 88 publications
(173 reference statements)
4
107
0
Order By: Relevance
“…Several natural compounds have been identified as electrophilic NRF2 inducers, like resveratrol, as we could also demonstrate in our results [ 33 ]. The stimulation of NRF2 by exogenous substances (e.g., sulforaphane) leads to a decreased translocation of NF- κ B to the nucleus, consistent with a lower DNA binding capacity and diminished proinflammatory action [ 34 ]. Nevertheless, NRF2 can also interact with CDKN1a , indicating that NRF2 is upregulated in cellular senescence [ 16 ], which goes in line with our observations, in particular after treatment with 50 μ M anthocyanidin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several natural compounds have been identified as electrophilic NRF2 inducers, like resveratrol, as we could also demonstrate in our results [ 33 ]. The stimulation of NRF2 by exogenous substances (e.g., sulforaphane) leads to a decreased translocation of NF- κ B to the nucleus, consistent with a lower DNA binding capacity and diminished proinflammatory action [ 34 ]. Nevertheless, NRF2 can also interact with CDKN1a , indicating that NRF2 is upregulated in cellular senescence [ 16 ], which goes in line with our observations, in particular after treatment with 50 μ M anthocyanidin.…”
Section: Discussionmentioning
confidence: 99%
“…When exposed to electrophiles or oxidative stress, cysteine residues of Keap1 are modified to prevent it from targeting NRF2 for proteasome degradation, resulting in rapid accumulation of NRF2 . CDKN1a can stimulate or promote NRF2 activation while p53 or p65 decrease NRF2 transcription [ 34 ]. CDKN1a protects cells against oxidative stress through upregulation of the NRF2 signaling pathway and may be the first defense mechanism used to reduce reactive oxygen species (ROS) under low stress conditions [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Literature data reported that polyphenols such as quercetin, ferulic acid, or caffeic acid are able to regulate Nrf2 production. [ 37,38 ] Sirota et al. [ 39 ] showed that caffeic acid induced Nrf2 translocation into the nucleus and consequently its transcription in ovarian carcinoma cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it might not be relevant to compare our data with plasma values since we have observed in preliminary experiments on rats that anthocyanins can rapidly accumulate into endothelial cells and, hence, most likely can reach much higher levels in intracellular cell compartments than in plasma. However, we also have to keep in mind the important hormetic effect of polyphenols, since they are able, at low concentrations, to stimulate the antioxydant Keap1/Nrf2/ARE system (including e-NOS) through moderate production of ROS [8,50]. Whatever the mechanism, endothelium-dependent vasodilation in both experimental models and humans has been observed after the intake of anthocyanin-rich fruit juices, indicating the ability of natural products to reach the endothelium [23].…”
Section: Discussionmentioning
confidence: 99%
“…Despite low oral bioavailability and rapid metabolism, polyphenols may, however, at cellular level produce-through moderate auto-oxidation-small amounts of reactive oxygen species (ROS), which induces an antioxidant adaptive response in cells through the activation of the Keap1/Nrf2/ARE pathway. This results to over-expression of genes coding for antioxidant enzymes (Antioxidant Response Element) [8]. The physiological mechanism most often put forward to explain cardiovascular protection due to polyphenols is their ability to regulate arterial blood pressure by maintaining or improving endothelial function [9,10].…”
Section: Introductionmentioning
confidence: 99%